Pharyngeal Bolus Transit During Swallowing Before and Short-Term After Thyroidectomy - Aneas, Geruza Costa Gonzaga; Nascimento, Weslania Viviane; Alves, Leda Maria Tavares; Pereira, Renata Escher; Freitas, Luiz Carlos Conti; Dantas, Roberto Oliveira (British Journal of Healthcare and Medical Research, 2022)
Background: Thyroid nodules are common in the population and may be associated with dysphagia. The surgical treatment of these nodules is a risk for lesion of cranial nerves branches with the possibility of swallowing and voice impairment. Dysphagia may be a complaint after the surgery even without nerves lesions. The objective of this investigation was to evaluate the pharyngeal bolus transit before and short-term after surgical treatment of thyroid nodules. Methods: Thirty-eight consecutive patients with thyroid nodules had videofluoroscopic evaluation of swallowing timing before the surgery. Dysphagia was a complaint in 20 (53%). In 21 (55%) the nodules were benign. Twenty-seven (71%) were submitted to total thyroidectomy. In 26 the swallow was also evaluated one to five days (median two days) after the surgery. The control group comprised 21 healthy volunteers. In videofluoroscopy patients and volunteers swallowed, in duplicate and random sequence, 5 mL and 10 mL of boluses of two consistencies, moderately thick and extremely thick. Results: Before the surgery patients had a delay in upper esophageal sphincter opening after the bolus arrived at the sphincter. After the surgery the patients had a shorter swallowing reaction time with 5 mL moderately thick bolus and shorter pharyngeal clearance with 10 mL extremely thick bolus. Conclusion: Before thyroid surgery patients with thyroid nodules had a delay in the upper esophageal sphincter opening related to bolus reach the sphincter. Few days after thyroidectomy there is an improvement of pharyngeal clearance of an extremely thick bolus.